(untitled) (Acta Judicial Journal, 2019)
The debate about the possibility of attributing functions in the execution process to other professionals who are not public officials is not something new. Arguments such as the slowness of the current enforcement procedure, the delays in its processing or a system of realization of the assets that does not fulfill its purpose of satisfying the creditor’s right are frequently repeated in the legal literature and in the discussion forums without to offer, in my modest opinion, a more efficient, agile and respectful solution with the rights of the parties in the procedure than the current one. The purpose of the enforcement process is, of course, to give full satisfaction to those who have been in possession of an executive title that entitles them to urge it. But not at any price or using any means, but taking into account that the defendant or executed is a subject of rights, which implies a process with all the guarantees and that the measures of enforcement or coercion adopted are proportional and proportionate to the intended purpose. That is to say, that there is a proper balance between collection of the credit and the limiting or expropriatory measure on the debtor’s patrimony.